2020
DOI: 10.1002/ardp.202000291
|View full text |Cite
|
Sign up to set email alerts
|

Potential antibacterial and antifungal activities of novel sulfamidophosphonate derivatives bearing the quinoline or quinolone moiety

Abstract: A series of new α‐sulfamidophosphonate/sulfonamidophosphonate ( 4a – n ) and cyclosulfamidophosphonate ( 5a – d ) derivatives containing the quinoline or quinolone moiety was designed and synthesized via Kabachnik–Fields reaction in the presence of ionic liquid under ultrasound irradiation. This efficient methodology provides new 1,2,5‐thiadiazolidine‐1,1‐dioxide derivatives 5a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 77 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In continuation of our previous research project [48,49] toward the development and synthesis of novel biomolecule compounds contain α-aminophosphonate moiety in high yields and clean conditions, in this study, we reported and used our previous strategy for the synthesis of new α-aminophosphonate (9a-h) and (10i-l) derivatives using the ionic liquid [TEAA] under US irradiation. We have found that the ionic liquid [TEAA] presented several advantages for the synthesis of α-aminophosphonate derivatives, such as giving pure product without chromatography purification and excellent yield in short reaction time with a simple workup.…”
Section: Chemistrymentioning
confidence: 99%
“…In continuation of our previous research project [48,49] toward the development and synthesis of novel biomolecule compounds contain α-aminophosphonate moiety in high yields and clean conditions, in this study, we reported and used our previous strategy for the synthesis of new α-aminophosphonate (9a-h) and (10i-l) derivatives using the ionic liquid [TEAA] under US irradiation. We have found that the ionic liquid [TEAA] presented several advantages for the synthesis of α-aminophosphonate derivatives, such as giving pure product without chromatography purification and excellent yield in short reaction time with a simple workup.…”
Section: Chemistrymentioning
confidence: 99%
“…A series of new α-sulfamidophosphonates and cyclosulfamidophosphonates incorporating quinoline or a quinolone moiety was synthesized by the Kabachnik–Fields reaction in the presence of a suitable ionic liquid under ultrasound irradiation [ 71 ].…”
Section: Kabachnik–fields Reactions With Dialkyl Phosphites Alkyl H -Phosphinates and Secondary Phosphine Oxidesmentioning
confidence: 99%
“…As a result of the literature review, some new quinoline derivatives that exhibited excellent antibacterial activity were used to design our target compounds, as shown in Figure 2. Bazin et al [51] reported the diethyl ((N-(4-bromophenyl) sulfamoyl) (2-chloro-8-methylquinolin-3-yl) methyl) phosphonate A to have a very potent activity against E. coli, with an MIC of 0.125 µg/mL. Moreover, the quinoline benzodioxole derivative B showed excellent antibacterial activity, with an MIC of 3.125 µg/mL against E. coli and S. aureus strains [52].…”
Section: Introductionmentioning
confidence: 99%